2011
DOI: 10.1002/cbf.1765
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone—induced haemoglobin changes and antioxidant enzymes response in erythrocytes

Abstract: Thyroid hormones modulate haemoglobin and reactive oxygen species (ROS) production, leading to antioxidant changes. This study evaluated the antioxidant response to ROS in erythrocytes in hypothyroid and hyperthyroid rats. Wistar rats were divided into four groups: control; hyperthyroid (T4-12 mg 1(-1) in drinking water); sham operated (simulation of thyroidectomy); and hypothyroid (thyroidectomized). Four weeks after, blood was collected and haemoglobin and T(4) levels, lipid peroxidation (LPO), protein oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
3
11
1
Order By: Relevance
“…This is in line with the results of Messarah et al [234] and [235] who observed no difference in SOD levels between hypothyroid rats and controls.…”
Section: Antioxidant Statussupporting
confidence: 93%
“…This is in line with the results of Messarah et al [234] and [235] who observed no difference in SOD levels between hypothyroid rats and controls.…”
Section: Antioxidant Statussupporting
confidence: 93%
“…This enzyme catalyzes the reduction of H 2 O 2 and organic hydroperoxides at the expense of glutathione. 24 Some authors have considered glutathione as an additional cofactor required for maximum activity of NO synthase, the enzyme responsible for synthesis of NO. 73 An increase in GPx activity induces greater consumption of glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, GPx is an important enzymatic mechanism for the disposal of peroxides, producing water or alcohol and reduced glutathione. 24 Nitric oxide may react with the superoxide radical and form peroxynitrite, a very deleterious nitrogen species, which may lead to lipid and protein peroxidation and damage. 17 In addition, NO has a modulatory role in pain states at both the central and peripheral levels.…”
mentioning
confidence: 99%
“…In addition, it showed that T3 therapy can increase the catalase activity and decrease the SOD activity in PTU-induced hypothyroid rats (Das and Chainy 2001). Another study showed that SOD and catalase activity in the erythrocytes of thyroidectomized rats remains unchanged (Araujo et al 2011). It has demonstrated that, some of anti-thyroid drugs such as PTU and methimazol have an antioxidant property; these drugs decrease the free radical generation in thyroid cell by reduction cytokine production (Hicks et al 1992;Weetman et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some other studies suggest that oxidative stress is increased in hypothyroidism and oxidize low density lipoprotein cholesterol (LDL-C) and finally prone to atherosclerosis (Sundaram et al 1997). Moreover, there is some controversial finding about the content and activity of enzymatic antioxidant in hypothyroidism; the studies showed that the increase or decrease or unchanged of SOD, catalase and glutathion peroxidase in hypothyroid patients (Das and Chainy 2001;Messarah et al 2007;Araujo et al 2011). To our knowledge, there is not any study demonstrating the effects of thyroid hormone replacement therapy by apelin and T4 or a combination of both on enzymatic antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%